Effects of FM0807, a novel curcumin derivative, on lipopolysaccharide-induced inflammatory factor release via the ROS/JNK/p53 pathway in RAW264.7 cells. Issue 5 (17th October 2018) - Wu, Yilong; Liu, Zhiwei; Wu, Weifang; Lin, Su; Zhang, Nanwen; Wang, Honglin; Tan, Shuangyu; Lin, Peimin; Chen, Xiaole; Wu, Lixian; Xu, Jianhua
Abstract : Purpose: Sepsis is a systemic inflammatory response caused by infection. Curcumin is known to have antioxidant and anti-inflammatory activities. FM0807, a curcumin derivative, was investigated in the present study to determine its effect on cytokines and the possible molecular mechanism.Main methods: The experiments were carried out in lipopolysaccharide (LPS)-induced RAW 264.7 cells. Cell viability was measured by MTT assay. ELISA, Griess assays, fluorescence-based quantitative PCR, flow cytometric analysis, 2′, 7′-dichlorodihydrofluorescein diacetate (DCFH-DA) experiments, and Western blotting were carried out to assess the potential effects of FM0807 on LPS-induced RAW 264.7 cells.Significant findings: FM0807 had no cytotoxic effects on RAW 264.7 cells. Furthermore, pretreatment with FM0807 inhibited the inflammatory factor tumor necrosis factor-α (TNF-α), interleukin (IL) 1β (IL-1β), IL-6, and inducible nitric oxide synthase (iNOS) at the protein and gene levels. FM0807 also inhibited the production of reactive oxygen species (ROS) and apoptosis. In addition, the activation of the ROS/JNK (c-jun NH2 -terminal kinase)/p53 signaling pathway was inhibited by FM0807 in RAW 264.7 cells in vitro .Conclusion: FM0807 has anti-inflammatory activity in vitro, which suggests a potential clinical application in sepsis. The anti-inflammatory activity of FM0807 may be mediated by the ROS/JNK/p53 signaling pathway.